Investigating groundwater: Middle school students' mapping data-driven, computer-based models to socio-hydrologic phenomena. Issue 1 (17th January 2022) - White, Holly; Lally, Diane; Forbes, Cory T.
Abstract: Groundwater is a critical component of the global water cycle and standards-based topic within science education. However, students articulate an array of ideas about groundwater systems, including their natural and human elements. One way to support students' learning about groundwater systems is through the use of data-driven, computer-based modeling tools in technology-enabled science learning environments. To use models to reason productively about groundwater, students must be able to interpret the relationship between the model and the phenomena it represents. Here, we report findings from a study conducted in 7th-grade classrooms (n = 209) during implementation of a 3-week curriculum module designed around a data-driven, computer-based groundwater modeling tool – the Hydrogeology Challenge. Students completed a series of tasks using the model to reason about and engage in problem-solving about a real-world, scenario-based water challenge. Here, we focus on how students relate – or map – elements of the model to the components of the authentic water-related phenomena they represent. We conducted quantitative and qualitative analyses of student artifacts and interviews. Findings suggest that students could more easily interpret and understand model elements which represent human dimensions of groundwater systems, such as wells, than they could elements that represent natural dimensions and processes, such as contour lines or groundwater flow direction. These findings provide important insights into students' model-based reasoning about groundwater and teaching and learning about coupled human-hydrological systems.